Pengaruh Risk Profile, Earnings, Dan Capital Terhadap Pertumbuhan Laba Pada Perbankan Di Bursa Efek Indonesia (Studi Kasus Pada Perbankan Di BEI Periode 2019-2021) - Sri Ayem; Umi Wahidah; Teguh Erawati; Inneke Dewi Karunia Putri (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This research aims to obtain empirical evidence regarding the risk profile, earnings, and capital’s impact on profit growth. The sample for this research consists of banking companies listed on the Indonesia Stock Exchange during the period of 2019-2021. The study includes a total of 39 data points. Data collection was conducted through the official website of IDX (Indonesia Stock Exchange) and the official websites of the banking companies listed on the Indonesia Stock Exchange during the period of 2019-2021. The data analysis technique used in this research is multiple linear regression analysis using SPSS 25.0 software. Multiple linear regression is used to examine the influence of independent variables (risk profile, earnings, and capital) on the dependent variable (earnings growth).The results of the data analysis show that partially, risk profile has a positive influence on earnings growth. This means that a better risk profile of banking companies tends to lead to increased earnings growth. However, partially, earnings and capital do not have a significant influence on earnings growth. This indicates that the financial performance of the company (in terms of income and capital) does not directly affect the earnings growth of banking companies. However, collectively (simultaneously), risk profile, earnings, and capital have a significant influence on earnings growth. This implies that when these three variables are combined in the analysis, they have an important impact on the earnings growth of banking companies. Keywords: Risk Profile, Earnings, Capital, Earnings Growth